2014
DOI: 10.1177/0960327114531994
|View full text |Cite
|
Sign up to set email alerts
|

Is one-time carbon monoxide intoxication harmless? Evaluation by argyrophilic nucleolar-organizing regions staining method

Abstract: In carbon monoxide (CO) poisoning, CO affects the oxygen-carrying capacity of the hemoglobin molecule. Nucleolar-organizing regions (NORs) are genetic loci on chromosomes that are composed of ribosomal DNA and proteins. NORs can be stained with silver. A total of 18 rats were exposed to CO in three different concentrations (1000, 3000, and 5000 ppm) with 6 rats as controls. The animals were euthanized 7 days after CO intoxication. Lung tissues were taken, embedded in paraffin blocks, and sectioned at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 27 publications
5
23
1
3
Order By: Relevance
“…NORs are surrounded by a great number of regulatory proteins in interphase and they are functional subunits of the nucleolus (23). We reported that the AgNOR protein amount increased depending on the increase of CO exposure (also it caused hypoxic condition) in the lung and heart cells in our previous studies (16)(17)(18). In our current study, the TAA/NA ratio and total AgNOR number per total nuclear number increased depending on the I/R injury in the tubular cells of kidney, too.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…NORs are surrounded by a great number of regulatory proteins in interphase and they are functional subunits of the nucleolus (23). We reported that the AgNOR protein amount increased depending on the increase of CO exposure (also it caused hypoxic condition) in the lung and heart cells in our previous studies (16)(17)(18). In our current study, the TAA/NA ratio and total AgNOR number per total nuclear number increased depending on the I/R injury in the tubular cells of kidney, too.…”
Section: Discussionsupporting
confidence: 63%
“…Bacause of the silver affi nity, those proteins are named argyrophilic NOR (AgNOR)-associated proteins and silver staining method is the most reliable to show nucleoli in interphase nuclei (6). A lot of studies have been carried out about the importance of AgNOR proteins such as benign and malignant thyroid tissue (7)(8)(9)(10)(11), hair root cells of humans with alopecia or healthy individuals (12,13), buccal epithelial cells of Down syndrome infants and healthy persons (14,15), the effects of CO exposure on the NOR protein synthesis of hearth and lung cells (16)(17)(18) and so on. However, to our knowledge, there are no researches in the literature about the association between AgNOR proteins and renal ischemia/reperfusion (IR) injury.…”
Section: Introductionmentioning
confidence: 99%
“…CO as a colorless, tasteless and odorless gas, produced by carbon or carbonaceous material combust insufficient in oxygen [3,4], is often overlooked by people. It is toxic to multiple organs such as lung, brain, kidney and so on [5].…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies on pregnant smokers, showing developmental harmful effects of CO on babies during pregnancy (9) Fatal death frequently occurs in severe CO poisoning (estimated fetal mortality is up to 36-67%) (10), because placenta delays fetal detoxification and also because fetal hemoglobin has greater affinity for CO than adult hemoglobin (3). Besides, some studies show that even one-time intrauterine exposure to CO may lead to intrauterine hypoxia, fetal brain damage and increased fetal death (11). In our country, the number of CO poisoning is also high because of inappropriate ventilation in indoor areas and domestic stoves (6,12,13).…”
Section: Epidemiology Of Carbon Monoxide Poisoningmentioning
confidence: 99%